1998
DOI: 10.3109/10826089809059332
|View full text |Cite
|
Sign up to set email alerts
|

HIV Risk Behaviors Associated with the Injection Process: Multiperson Use of Drug Injection Equipment and Paraphernalia in Injection Drug User Networks

Abstract: This study examines drug acquisition and multiperson use of paraphernalia, drugs, and needles/syringes. Ethnographers observed 54 injection episodes in which IDUs were linked by HIV risk behaviors, and developed a typology of higher-risk, lower-risk, and nonsharing-risk networks. Multiperson use of injection paraphernalia or drug solution occurred in most injection events (94%). Serial use of syringes/needles occurred infrequently (14%) relative to "backloading" (37%) and reuse of paraphernalia (cookers 84%, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…The potential link between drug sharing and blood-borne disease transmission has been described (Bourgois et al, 1997;Bourgois, 1999;Finlinson et al, 2000;Finlinson et al, 2005;Friedman et al, 1999;Grund et al, 1991;Grund et al, 1996;Inciardi and Page, 1991;Jose et al, 1993;Koester and Hoffer, 1994;Koester et al, 1996a;Koester 1998;Needle et al, 1998;Page et al, 1990;Page, 1999;Zule, 1992) and shown to occur more frequently than syringe sharing (Koester et al, 1996b;Friedman et al, 1997). Recently, a study by Colón and his colleagues found that jointly purchasing drugs was significantly associated with risky drug preparation behaviors among IDU in Puerto Rico and New York City (2001).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The potential link between drug sharing and blood-borne disease transmission has been described (Bourgois et al, 1997;Bourgois, 1999;Finlinson et al, 2000;Finlinson et al, 2005;Friedman et al, 1999;Grund et al, 1991;Grund et al, 1996;Inciardi and Page, 1991;Jose et al, 1993;Koester and Hoffer, 1994;Koester et al, 1996a;Koester 1998;Needle et al, 1998;Page et al, 1990;Page, 1999;Zule, 1992) and shown to occur more frequently than syringe sharing (Koester et al, 1996b;Friedman et al, 1997). Recently, a study by Colón and his colleagues found that jointly purchasing drugs was significantly associated with risky drug preparation behaviors among IDU in Puerto Rico and New York City (2001).…”
Section: Introductionmentioning
confidence: 91%
“…Indirect or syringe-mediated sharing practices that may facilitate human immunodeficiency virus (HIV), hepatitis B (HBV) and hepatitis C (HCV) transmission include the preparation and distribution of jointly purchased drugs for injection as well as the communal use of injection paraphernalia, such as drug mixing containers ("cookers" or "spoons"), cotton filters, and water for mixing the drug into solution and for rinsing syringes (Bourgois et al, 1997;Bourgois, 1999;Finlinson et al, 2000;Finlinson et al, 2005;Friedman et al 1999;Grund et al, 1991;Grund et al, 1996;Inciardi and Page, 1991;Jose et al, 1993;Koester et al, 1990;Koester and Hoffer, 1994;Koester et al, 1996b;Koester, 1998;Needle et al, 1998;Page, 1990;Page et al, 1990;Zule, 1992). While intervention programs have responded to these latter risks with prevention messages and intervention materials such as safer injection kits containing multiple vials of water, dental cottons, and metal caps for use as cookers, little has been done to address the transmission risks embedded within the process of preparing and apportioning shared drugs.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The 1-month timeframe of risk behavior assessment was used for questions most likely to be affected by recall. Questions were developed using information from the recruitment sites and expert opinion and were also modeled on several sources such as previously validated questionnaires about injection drug use and determinants of HCV risk among IDUs (Cox et al, 2002;Koester, Booth, and Zhang, 1996;Needle et al, 1998). The initial questionnaire was pilot tested with 86 subjects in the target population prior to the start of the study and adjusted according to participant feedback.…”
Section: Data Collectionmentioning
confidence: 99%
“…Joint preparation often includes the additional DPP of using a single syringe to measure the amount of water to be used in dissolving the drug and to divide and distribute the drug solution. Joint preparation has been found to be particularly common among IDUs preparing 'speedballs' (i.e., cocaine and heroin solutions) and has been linked to the practice of pooling money to procure drugs among two or more IDUs (Colon et al, 2001a;Grund et al, 1991;Koester and Hoffer, 1994;Needle et al, 1998).…”
Section: Introductionmentioning
confidence: 97%